Profit efficiency among catfish marketers in Lagos state, Nigeria: a Stochastic Profit Frontier Analysis (SPFA) approach - Settings Kazeem , Aboaba (Applied Studies in Agribusiness and Commerce, 2021)
The study analyzed the determinants of profit efficiency among catfish marketers in Lagos state, Nigeria. Multistage sampling procedure was used to select 120 catfish marketers, data were collected with the aid of a structured questionnaire. The data collected were analyzed with the use of descriptive statistics, enterprise budgetary technique, Shephered-Futrell method and stochastic profit frontier analysis (SPFA) model. The result of the gross ratio and net return on investment reveals that catfish marketing was a profitable and bankable enterprise. About 76.72% of sales revenue was taken up by the costs. The SPFA reveals that cost of catfish purchased and depreciation cost had positive (p<0.01) effects on profit while transportation cost (p<0.01) and labour cost (p<0.05) had negative effects. Furthermore, marital status and credit use (p<0.01) had negative effects on profit inefficiency, the mean profit efficiency of the catfish marketers was 74%. The study concluded that catfish marketers were inefficient, however, to improve the efficiency of the marketers and create more job opportunities; the study recommends that credit facilities that will enable the marketers increase their scale of operation, acquire better marketing resources and employ capable hands in catfish marketing should be made available and accessible. Policies that will help to provide good road networks and reduce the pump price of premium motor spirit (PMS) should be given adequate consideration.